2010
DOI: 10.1158/0008-5472.can-09-3468
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ASF/SF2 as a Critical, Allele-Specific Effector of the Cyclin D1b Oncogene

Abstract: The cyclin D1b oncogene arises from alternative splicing of the CCND1 transcript, and harbors markedly enhanced oncogenic functions not shared by full-length cyclin D1 (cyclin D1a). Recent studies showed that cyclin D1b is selectively induced in a subset of tissues as a function of tumorigenesis; however, the underlying mechanism(s) that control tumor-specific cyclin D1b induction remain unsolved. Here, we identify the RNA-binding protein ASF/SF2 as a critical, allele-specific, disease-relevant effector of cyc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 39 publications
2
61
0
Order By: Relevance
“…While preliminary, this observation suggests a novel regulatory loop between D-cyclins and SF2. Moreover, robust and transient SF2 over-expression verified altered D-cyclin splicing [consistent with recently published data (8)] and the transcription of known SF2-associated genes (e.g., CLK1 and C1qBP) while having minimal impact on genes not known to be associated with SF2 (e.g., KHDRBS3). These data will provide valuable information related to dissecting signaling pathways as part of the future studies.…”
Section: Recent Accomplishments (Fromsupporting
confidence: 87%
See 1 more Smart Citation
“…While preliminary, this observation suggests a novel regulatory loop between D-cyclins and SF2. Moreover, robust and transient SF2 over-expression verified altered D-cyclin splicing [consistent with recently published data (8)] and the transcription of known SF2-associated genes (e.g., CLK1 and C1qBP) while having minimal impact on genes not known to be associated with SF2 (e.g., KHDRBS3). These data will provide valuable information related to dissecting signaling pathways as part of the future studies.…”
Section: Recent Accomplishments (Fromsupporting
confidence: 87%
“…Published data have suggested that SF2 and cyclin D1 isoforms have oncogenic functions (6,7) suggesting a potential link between splicing and proliferation. Based on preliminary data (now published (8)), the current proposal is geared towards determining the consequence of SF2 function and splicing in the context of PCa.…”
Section: Introductionmentioning
confidence: 99%
“…While the G870A polymorphism appears to affect the production of D1b in normal tissues, in cancer cells production of D1b occurs regardless of the identity of the final E4 nucleotide (Olshavsky et al 2010). Consistent with this, RBPs that influence the choice between D1a and D1b have also been identified.…”
Section: Cyclin D1mentioning
confidence: 63%
“…A strong correlation between Sam68 expression levels and D1b production was also observed, underscoring the biological significance of these findings. The SR protein SRSF1 (formerly ASF/SF2) has also been shown to bind preferentially to the D1b transcript and promote the production of D1b, and SRSF1 levels were also found to correlate with D1b production (Olshavsky et al 2010). The effects of SRSF1 on D1b production were enhanced with the 870G allele, potentially providing an explanation for the fact that, in cancer, both alleles result in similar D1b production.…”
Section: Cyclin D1mentioning
confidence: 99%
“…The alternatively spliced transcripts of Bcl-2-like 1 (BCL2L1) and myeloid cell leukemia 1 (MCL-1) genes encode either the anti-apoptotic or pro-apoptotic isoforms that manipulate the therapeutic response of cancer cells (Moore et al 2010;Gautrey and Tyson-Capper 2012). The inclusion of cyclin D intron 4 leads to the production of the cyclin D1b isoform which acts as an oncogene in prostate cancer cells (Burd et al 2006;Olshavsky et al 2010). An increase in the short S6K1 variant facilitates the transformation of breast epithelial cells, whereas the presence of the long S6K1 isoform mediates the opposite effect by inhibiting Ras-induced transformation and tumor growth (Ben-Hur et al 2013).…”
Section: Introductionmentioning
confidence: 99%